Evaluation of the Condom Barriers Scale for Young Black MSM: Reliability and Validity of Three Sub-Scales - Crosby, Richard (Sex Transm Dis, 2017)
BACKGROUND: Reliable and valid scale measures of barriers to condom use are not available for young Black MSM (YBMSM). The purpose of this study was to evaluate the Condom Barriers Scales for application with YBMSM. METHODS: A clinic-based sample of 600 YBMSM completed a computer-assisted self-interview. The primary measure was a 14-item abbreviated version of the Condom Barriers Scale. Reliability and criterion validity were assessed. RESULTS: All three sub-scales were reliable: partner-related barriers (Cronbach’s alpha=.73), sensation-related barriers (alpha=.70), and motivation-related barriers (alpha=.81). A complete absence of barriers was common: 47.0% (partner-related), 30.7% (sensation-related), and 46.5% (motivation-related). Dichotomized sub-scales were significantly associated with reporting any condomless insertive anal sex (all=P < .001) and any condomless receptive anal sex (all=P < .001). The sub-scales were significantly associated with these measures of condomless sex preserved at a continuous level (all=P <.001, except for sensation barriers associated with condomless receptive anal sex =.03). Further, the sub-scales were significantly associated with reporting any condom use problems (all =P <.001) and a measure of condomless oral sex (all =P <.001, except for partner-related barriers =.31). Finally, the sensation-related barriers sub-scale was significantly associated with testing positive for Chlamydia and/or gonorrhea (P=.049). CONCLUSIONS: The three identified sub-scales yielded adequate reliability and strong evidence of validity, thereby suggesting the utility of these brief measures for use in observational and experimental research with YBMSM.